2018
DOI: 10.1016/j.actbio.2017.11.024
|View full text |Cite
|
Sign up to set email alerts
|

Injectable nanocomposite cryogels for versatile protein drug delivery

Abstract: Here we present an injectable nanocomposite hydrogel for simple and versatile controlled release of therapeutic proteins. Protein release from hydrogels often requires first entrapping the protein in particles and embedding these particles within the hydrogel to allow controlled protein release. This pre-encapsulation process can be cumbersome, can damage the protein's activity, and must be optimized for each protein of interest. The strategy presented in this work simply premixes the protein with charged nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
99
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 140 publications
(102 citation statements)
references
References 34 publications
(46 reference statements)
2
99
0
Order By: Relevance
“…The Mooney group followed up with a similar hydrogel system in 2018 to deliver BDC peptide antigens to dendritic cells to induce regulatory T cells via two methods: i) encapsulated in PLG microparticles within the gel or ii) directly conjugated to the alginate gel . In the same year, the authors developed a photoclickable alginate gel containing laponite (a charged nanocomposite on which proteins can adsorb) for the prolonged release of cytokines, reducing burst release effects and extending their release over several weeks …”
Section: Macroscale Materials For Immunotherapymentioning
confidence: 99%
“…The Mooney group followed up with a similar hydrogel system in 2018 to deliver BDC peptide antigens to dendritic cells to induce regulatory T cells via two methods: i) encapsulated in PLG microparticles within the gel or ii) directly conjugated to the alginate gel . In the same year, the authors developed a photoclickable alginate gel containing laponite (a charged nanocomposite on which proteins can adsorb) for the prolonged release of cytokines, reducing burst release effects and extending their release over several weeks …”
Section: Macroscale Materials For Immunotherapymentioning
confidence: 99%
“…Currently, the controlled release of proteins has been regarded as a key to maximize the therapeutic effect of growth factors. To generate a controlled release system, diverse kinds of hydrogels or cryogels were applied to protein delivery to increase immobilization and localization of proteins . Herein, we used heparin as one of the biomaterials of cryogels to support VEGF‐ADSCs offering enhanced captivity of VEGF through heparin's specific binding affinity to VEGF.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, cryogels could be made using biopolymers with intrinsic antimicrobial activity, such as chitosan (Khan et al, 2019). Koshy et al (2018) demonstrated that injectable cryogel is able to incorporate and release various molecules to mediate their biological activities. Based on published data of the anti-inflammatory and prohealing properties of IL-10 and TGF-β as well as the angiogenic and regenerative properties of VEGF and FGF, these growth factors and cytokines (GF/C) were used in the current study.…”
Section: Introductionmentioning
confidence: 99%